Transforming Islamic Da’wah Institutions for Achieving SDG 4 and SDG 16: A Strategic Management Perspective - Meity Suryandari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This conceptual study examines how Islamic Da’wah institutions can be strategically transformed to effectively contribute to the achievement of Sustainable Development Goals (SDGs), particularly Goal 4 on quality education and Goal 16 on peace, justice, and strong institutions. Grounded in strategic management principles and the ethical foundations of Islamic thought, especially maqashid shariah (the objectives of Islamic law), the paper presents a model that integrates religious values into institutional planning and reform. By conducting a thorough review of existing literature, the study identifies and synthesizes essential components for transformation, including visionary leadership that prioritizes long-term impact, ethical governance rooted in transparency and accountability, and inclusive education that is both accessible and values-based. The analysis reveals that aligning Islamic ethical frameworks with global development goals can enhance the operational effectiveness and social relevance of Da’wah institutions. Moreover, the incorporation of maqashid shariah in organizational strategy promotes a holistic approach to development that balances spiritual and material objectives. The study argues that by embracing strategic planning processes that reflect both Islamic values and modern development practices, Da’wah institutions can play a crucial role in advancing educational equity and institutional integrity. This not only strengthens the legitimacy and sustainability of these organizations but also positions them as key partners in the broader development agenda. Ultimately, the paper contributes to ongoing discussions about the role of faith-based organizations in global development by offering a conceptual framework that bridges Islamic governance principles with the pursuit of sustainable development outcomes, encouraging a more integrated and ethically grounded approach to institutional reform.